Trends in the development of agriculture in the years after the independence of the Republic of Kazakhstan (1991-2009) (Journal of Geography and Environmental Management, 2020)
This article presents problems associated with the development of agriculture in the Republic of Kazakhstan in the period of independence to the present day. Agriculture is one of the important sectors of the economy of Kazakhstan. The problem of food is a global problem. In many developed countries, there is considerable support for agriculture. The development of agricultural production sectors demonstrates the level of evolution and spread of new technologies, the level of the food supply of the countries. The Republic of Kazakhstan is in a number of countries leading in the production of agricultural raw materials because it is located on the territory where can be engaged in extensive agriculture. First, it is one of the factors determining the strategy of the socio-economic development of the country. Secondly, it has a great impact on the food security of the country. It is known that the agriculture of Kazakhstan in 1991-2009 had undergone significant changes due to the transition to new economic conditions. Specifically, the new economic situations have had a strong impact on livestock and crop production. In connection with the extensive privatization carried out in the Republic, many production facilities and enterprises were transferred to private ownership. In this article, there are presented the initial conditions for the development of animal husbandry and identified changes in this industry in the new economic conditions in the period from 1991 to 2010. The study has revealed that the changes occurred within three periods. Period of transition to new economic conditions (the first period – 1991), privatization of industries and production (the second period – 1995-1996), the privatization of the remaining state agricultural enterprises (the third period – 1998).
Keywords: agriculture, reform, food supply, privatization, agrarian sector, market relations.